2020
DOI: 10.1111/nmo.13949
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of gastric electrical stimulation in intractable nausea and vomiting at 10 years: A retrospective analysis of prospectively collected data

Abstract: Background: Gastric electrical simulation has been shown to relieve nausea and vomiting in medically refractory patients. Efficacy of gastric electrical stimulation has been reported mostly in short-term studies, but none has evaluated its efficacy beyond 10 years after implantation. Methods: Patients implanted at our center for medically refractory severe and chronic nausea and/or vomiting were evaluated before and over 10 years after implantation using symptomatic scale and quality of life (GIQLI) score. Imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…A meta-analysis including up to 600 patients showed an improvement in total symptom severity score, nausea, vomiting, early satiety, and loss of appetite ( Chu et al, 2012 ). Long-term studies evidenced that clinical efficacy was seen even after 5 and 10 years of follow-up in more than 50% of patients in an intention to treat follow-up ( McCallum et al, 2011 ; Gourcerol et al, 2012 ; Hedjoudje et al, 2020 ). GES was shown to reduce hospitalization requirements, nutritional status, and HbA1c ( Abell et al, 2003a ).…”
Section: Clinical Efficacy Of Enterra Therapymentioning
confidence: 99%
“…A meta-analysis including up to 600 patients showed an improvement in total symptom severity score, nausea, vomiting, early satiety, and loss of appetite ( Chu et al, 2012 ). Long-term studies evidenced that clinical efficacy was seen even after 5 and 10 years of follow-up in more than 50% of patients in an intention to treat follow-up ( McCallum et al, 2011 ; Gourcerol et al, 2012 ; Hedjoudje et al, 2020 ). GES was shown to reduce hospitalization requirements, nutritional status, and HbA1c ( Abell et al, 2003a ).…”
Section: Clinical Efficacy Of Enterra Therapymentioning
confidence: 99%
“…In addition to pharmaceutical compounds in the pipeline, neuromodulation and endosurgical techniques, such as gastric peroral endoscopic myotomy (G-POEM), may help address refractory. Endoscopic pyloromyotomy appears to be effective in the short term, especially for nausea and vomiting, but further study is needed to accurately identify the subset of gastroparesis patients who have pyloric dysfunction, and long-term results must be assessed [ 15 , 4 ] (Figure 5 ).…”
Section: Reviewmentioning
confidence: 99%
“…The gastric pacemaker has been shown to help alleviate these symptoms, as described in the studies in our review [ 18 ]. A study conducted between 1998 to 2009 on 50 patients revealed that there was an improvement in nausea (2.46 vs. 1.35, P =.001) and vomiting (3.35 vs. 1.49, P<0.001) [ 15 ]. In another study conducted on 13 patients by Laine et al showed that before implantation, 13 had severe nausea, 11 had severe vomiting.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations